(untitled) - Aiken, Clay (New York, 2004)
When he was a kid singing in his church choir, Clay Aiken never dreamed of becoming a pop music star. His ambition was to be a teacher, maybe even a high school principal. But the music that was Clay's joy in life was destined to lead him to unexpected triumphs...
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy